Fluorine-containing nano protective coating as well as preparation method and application thereof
By using modified Ti3C2-MXenes to compound wrinkled graphene oxide and coupling reaction with fluoro-containing siloxane and sulfur-containing silane coupling agent, nanomodifiers were prepared, which solved the problem of complex and high cost of the existing transparent superhydrophobic coating preparation method, and achieved fluoro-containing nanoprotective coatings with low porosity and high mechanical strength, with wide industrial application prospects.
Patent Information
- Application Number
- CN202510049724.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing methods for preparing transparent superhydrophobic coatings are complex, costly, and require harsh chemical conditions and processes, which limit their wide application in industry.
Ti3C2-MXenes is used as the core material, modified by tannin acid and compounded with wrinkled graphene oxide, combined with fluoro-containing silicone and sulfur-containing silane coupling agent for coupling reaction, and prepared nanomodifiers, mixed with polyurethane resin and other materials, evenly applied to the surface of the electronic motherboard, and ventilated and cured to produce a fluoro-containing nanoprotective coating.
The prepared fluorine-containing nanoprotective coating has the advantages of low porosity, low ash content, large mechanical strength, and high volume density. It has significantly improved life and low resistivity, and has broad application prospects.
Smart Images

Figure BDA0005239619000000131 
Figure BDA0005239619000000142 
Figure BDA0005239619000000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a fluorine-containing nano protective coating and a preparation method and application thereof. Background Art
[0002] Super-hydrophobic (static contact angle of the surface is greater than 150°) coatings have the properties of water resistance, anti-pollution, anti-oxidation, and self-cleaning, and therefore have attracted much attention. Transparent super-hydrophobic coatings not only have the properties of super-hydrophobic surfaces but also have good visible light transmittance. They are used in outdoor optoelectronic and display equipment, self-cleaning glass of high-rise buildings, and as windshields for cars and airplanes, etc., and have great application value.
[0003] Currently, there are not many studies on transparent super-hydrophobic coatings, and the preparation methods mainly include sol-gel method, phase separation method, self-assembly method and plasma method.
[0004] There are methods for preparing super-hydrophobic coatings by the sol-gel method. For example, Chinese invention patent application CN101362632A prepares a transparent film by immersing a transparent substrate material into a sol prepared by chelating organic aluminum salts by the sol-gel method by a pulling method; Nakajima A et al. (Adv Mater. 1999, (11): 1365-1368) add a sublimable powdered compound Al(C2H7O2)3 to a silica sol or an aluminum sol to prepare a transparent coating. These coatings all need to be heat-treated to obtain a certain degree of roughness and then modified with extremely low free energy perfluoroalkyl chlorosilane or perfluoroalkyl alkoxysilane to obtain a transparent highly hydrophobic coating. HM Shang et al. (Thin Solid Films. 2005, (472): 37-43) used TEOS, MPS and MTES as raw materials, and coated the silica sol obtained by hydrolysis on the surface of a glass slide. The silica sol was then self-assembled under the action of CTMS and TFCS. The transparency of the formed silicon-based transparent film was higher than 90%, and the maximum contact angle reached nearly 165°.
[0005] Methods for preparing super hydrophobic coatings by plasma method, for example, Hozumi et al. (Thin Solid Films. 1997, 303: 222-225) used chemical vapor deposition (CVD) method to make the surface of the deposited film obtain a certain roughness, and then used silane containing perfluoroalkyl as gas source, and obtained a transparent super hydrophobic film by plasma treatment. Li Guoxing et al. (Applied Surface Science. 2008, (254): 5299-5303) used magnetron sputtering technology to deposit boron nitride film on silicon substrate surface, and then obtained a double-scale roughness on the surface by CF4 plasma treatment, and obtained a transparent super hydrophobic film with a contact angle of 159°.
[0006] The method of preparing super hydrophobic coating by self-assembly method, for example, Javier Bravo et al. (Langmuir. 2007, (23): 7293-7298) used LBL self-assembly method to dip-coat three layers on the surface of glass slide, the first adsorption layer is PAH / SPS, which enhances the binding force between polymer and nanoparticles; the middle layer is PAH / silicon dioxide (50+20nm), which provides the dual-scale roughness structure required for super hydrophobicity; the top layer is PAH / silicon dioxide (20nm), and the surface free energy of the film is reduced by silane. The contact angle of the film is 160°, the receding angle is less than 10°, and the optical transmittance is higher than 90% in the visible light region. Chinese invention patent CN101519278B assembles negatively charged oxide nanoparticles and cationic polymer LBL layer by layer. Although the transmittance is very high, the process is complicated and needs to be modified with low surface energy long-chain perfluorosilane by chemical deposition after sintering at 400°C. The raw materials are expensive and the conditions are harsh. Chinese invention patent CN101407648B deposits silica colloid onto conductive glass by electrophoresis. It has high transmittance but cannot be prepared on a large scale.
[0007] The above coating method has complex preparation process, high cost, and requires harsh chemical conditions and processes, which limit the wide application of super-hydrophobic coating in industry. Therefore, a method for transparent super-hydrophobic surface with simple operation, easy raw materials, and large-scale preparation and application is needed. Summary of the invention
[0008] The purpose of the present invention is to propose a fluorine-containing nano protective coating and its preparation method and application. The preparation method is simple, prevents the polarization of the carbon anode plate, has the advantages of low porosity, low ash content, high mechanical strength, high volume density, etc., significantly improved service life, low resistivity, etc., and has broad application prospects.
[0009] The technical solution of the present invention is achieved in this way:
[0010] The present invention provides a method for preparing a fluorine-containing nano protective coating. The surface of Ti3C2-MXenes is modified with tannic acid, coated with wrinkled graphene oxide, coupled with fluorine-containing siloxane and sulfur-containing silane coupling agents, reduced, and subjected to surface click reaction to obtain a nano modifier, which is evenly mixed with a polyurethane resin, a dispersant, a defoaming agent and a solvent, evenly applied to the surface of an electronic mainboard, and ventilated and cured to obtain a fluorine-containing nano protective coating.
[0011] As a further improvement of the present invention, the following steps are included:
[0012] S1. Preparation of modified Ti3C2-MXenes: adding Ti3C2-MXenes to water, adding tannic acid and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain modified Ti3C2-MXenes;
[0013] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: Add modified Ti3C2-MXenes and graphene oxide into water, disperse them uniformly by ultrasonication, spray dry them, and ball mill them to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0014] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: adding fluorinated siloxane and sulfur-containing silane coupling agent into ethanol, adding wrinkled graphene oxide @Ti3C2-MXenes, heating and stirring to react, centrifuging, washing, and drying to obtain modified wrinkled graphene oxide @Ti3C2-MXenes;
[0015] S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes is reduced by hydrazine hydrate vapor to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0016] S5. Click chemistry reaction: adding modified wrinkled graphene @Ti3C2-MXenes, 2,2-dimethoxy-2-phenylacetophenone, and methyl acrylate into N,N-dimethylformamide, irradiating with ultraviolet light, centrifuging, washing, and drying to obtain a nano-modifier;
[0017] S6. Preparation of fluorine-containing nano protective coating: stir and mix the nano modifier, polyurethane resin, dispersant, defoaming agent and solvent evenly, apply evenly to the surface of the electronic mainboard, and maintain under ventilation to obtain the fluorine-containing nano protective coating.
[0018] As a further improvement of the present invention, the mass ratio of Ti3C2-MXenes, tannic acid and catalyst in step S1 is 10:3-5:0.5-1, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4h, and the catalyst is a Tris-HCl solution with a pH of 8-9.
[0019] As a further improvement of the present invention, the mass ratio of the modified Ti3C2-MXenes and graphene oxide in step S2 is 3-5:2-3.
[0020] As a further improvement of the present invention, the mass ratio of the fluorinated siloxane, the sulfur-containing silane coupling agent, and the wrinkled graphene oxide @Ti3C2-MXenes in step S3 is 3-5:1-2:10, the temperature of the heated stirring reaction is 45-55°C, the time is 1-3h, and the fluorinated siloxane is selected from 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyl trimethoxysilane, dodecafluoroheptyl propyl trimethoxysilane, dodecafluoroheptyl propyl methyl dimethoxysilane, 3,3,3-trifluoropropyl methyl dimethoxysilane, 3 , at least one of 3,3-trifluoropropyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane or 1H,1H,2H,2H-perfluorooctyltrimethoxysilane. Preferably, the fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane in a mass ratio of 8-10:2-3. The sulfur-containing silane coupling agent is at least one of bis-(3-triethoxysilylpropyl)tetrasulfide, bis-(3-triethoxysilylpropyl)disulfide, mercaptopropyltriethoxysilane and γ-mercaptopropyltrimethoxysilane.
[0021] As a further improvement of the present invention, the time for the hydrazine hydrate steam reduction in step S4 is 7-10 hours.
[0022] As a further improvement of the present invention, the mass ratio of the modified wrinkled graphene @Ti3C2-MXenes, 2,2-dimethoxy-2-phenylacetophenone, and methyl acrylate in step S5 is 10:0.03-0.05:4-6, and the ultraviolet lamp irradiation time is 40-60s.
[0023] As a further improvement of the present invention, the mass ratio of the nano modifier, polyurethane resin, dispersant, defoamer and solvent in step S6 is 10-12:85-105:2-3:1-2:100-200, the solvent is selected from at least one of acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, dichloromethane, tetrahydrofuran, N,N-dimethylformamide and dioxane, the dispersant is selected from at least one of oleyl amino oleate, polyethylene glycol 600, polyethylene glycol 400 and sodium oleate, and the defoamer is selected from at least one of propylene glycol, isopropanol, n-butanol, isooctyl alcohol, naphtha and white mineral oil.
[0024] The present invention further protects a fluorine-containing nano protective coating prepared by the above preparation method.
[0025] The present invention further protects the use of the above-mentioned fluorine-containing nano protective coating in the preparation of waterproof electronic products.
[0026] The present invention has the following beneficial effects:
[0027] The present invention uses two-dimensional transition metal carbon titanium compound Ti3C2-MXenes as the core material. Through the weak interaction of interlayer van der Waals force, the prepared coating has good self-lubrication, wear resistance and other characteristics, and at the same time, has good modifiable performance. Through tannic acid surface modification, the two-dimensional material can be compounded with graphene oxide to form a composite. After spray drying, the solvent on the surface of the droplet evaporates rapidly, resulting in changes in surface tension, causing uneven contraction of the surface of the droplet, thereby forming a wrinkled structure, simulating the micron and nanometer-level rough structure of the surface of "petals" and "lotus leaves", thereby greatly improving the surface hydrophobicity of the coating. In addition, the hydroxyl group of the surface graphene oxide can also be modified by coupling reaction with fluorine-containing siloxane and sulfur-containing silane coupling agent, thereby connecting the fluorine-containing structure to the nanostructure, and at the same time, introducing a thiol group. On the one hand, the fluorine-containing structure greatly improves the high and low temperature resistance, waterproof, anti-fouling, self-cleaning, weather resistance, corrosion resistance, anti-ultraviolet aging, antistatic and wear resistance of the coating, thereby greatly improving the comprehensive performance of the coating. In addition, when the surface fluorosilane is damaged, the nanomodifiers in the pores will move to the coating surface, thereby repairing the superhydrophobic surface and achieving its self-healing properties.
[0028] After being reduced with hydrazine hydrate vapor, graphene oxide is reduced to a graphene layered structure. Graphene has an ultra-thin thickness, good anti-friction and wear resistance, and a small friction coefficient. It is a solid lubricating material with relatively stable properties, which makes the coating have better self-lubrication and wear resistance.
[0029] The prepared modified wrinkled graphene @Ti3C2-MXenes was subjected to click chemistry reaction, reacted with ene ester, and polyacrylate hydrophobic groups were connected to the surface of the nano-modifier, etc., which improved the mechanical properties of the coating and further formed an uneven micro-nanoscale rough structure layer, which can increase the specific surface area of the surface and provide the necessary physical basis for the realization of super-hydrophobic properties. At the same time, it has a lower surface energy, which helps to increase the contact angle of water droplets, making it easier for water droplets to form spheres on the surface, and can also improve the binding ability with the substrate to form a stable chemical bond, which can resist the erosion of chemical substances such as acid, alkali, and salt spray, and has a self-cleaning function, which can use rainwater or water flow to take away dust and dirt on the surface. The introduction of the carbon polymer layer can further improve the self-cleaning effect of the surface, making it more convenient to maintain in practical applications.
[0030] The fluorine-containing nano protective coating prepared by the present invention greatly improves the high and low temperature resistance, waterproofness, anti-fouling, self-cleaning, weather resistance, corrosion resistance, resistance to ultraviolet aging, antistatic and wear resistance of the coating by adding a nano modifier, and the mechanical properties are enhanced, the adhesion is improved, and it is used for surface coating of electronic materials to improve the durability of the material, and has broad application prospects. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Graphene oxide, with a sheet diameter of 2-5 μm, a monolayer rate of >99%, a thickness of 0.8-1.2 nm, and a purity of >99%, was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0033] Example 1
[0034] This embodiment provides a method for preparing a fluorine-containing nano protective coating, comprising the following steps:
[0035] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 3 g of tannic acid and 0.5 g of catalyst were added, heated to 40 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0036] The catalyst is a Tris-HCl solution with a pH of 8;
[0037] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 3 g of modified Ti3C2-MXenes and 2 g of graphene oxide were added to 100 mL of water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0038] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 3 g of fluorinated siloxane and 1 g of sulfur-containing silane coupling agent were added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes was added. The mixture was heated to 45°C, stirred for 1 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes.
[0039] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 8:2;
[0040] S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes was reduced with hydrazine hydrate vapor for 7 h to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0041] S5. Click chemistry reaction: 10 g of modified wrinkled graphene @Ti3C2-MXenes, 0.03 g of 2,2-dimethoxy-2-phenylacetophenone, and 4 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 40 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0042] S6. Preparation of fluorine-containing nano protective coating: 10 g of nano modifier, 85 g of polyurethane resin, 2 g of polyethylene glycol 600, 1 g of n-butanol and 100 g of acetone were stirred and mixed for 15 min, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0043] Example 2
[0044] This embodiment provides a method for preparing a fluorine-containing nano protective coating, comprising the following steps:
[0045] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 5 g of tannic acid and 1 g of catalyst were added, heated to 50 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0046] The catalyst is a Tris-HCl solution with a pH of 9;
[0047] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 5 g of modified Ti3C2-MXenes and 3 g of graphene oxide were added to 100 mL of water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0048] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 5 g of fluorinated siloxane and 2 g of γ-mercaptopropyltrimethoxysilane were added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes were added. The mixture was heated to 55°C, stirred for 3 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes.
[0049] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 10:3;
[0050] S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes was reduced with hydrazine hydrate vapor for 10 h to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0051] S5. Click chemistry reaction: 10 g of modified wrinkled graphene @Ti3C2-MXenes, 0.05 g of 2,2-dimethoxy-2-phenylacetophenone, and 6 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 60 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0052] S6. Preparation of fluorine-containing nano protective coating: 12 g of nano modifier, 105 g of polyurethane resin, 3 g of polyethylene glycol 600, 2 g of white mineral oil and 200 g of methyl ethyl ketone were stirred and mixed for 15 minutes, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0053] Example 3
[0054] This embodiment provides a method for preparing a fluorine-containing nano protective coating, comprising the following steps:
[0055] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 4 g of tannic acid and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0056] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0057] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 4 g of modified Ti3C2-MXenes and 2.5 g of graphene oxide were added to 100 mL of water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0058] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 4 g of fluorinated siloxane and 1.5 g of mercaptopropyl triethoxysilane were added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes was added, heated to 50°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes;
[0059] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 9:2.5;
[0060] S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes was reduced with hydrazine hydrate vapor for 8 h to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0061] S5. Click chemistry reaction: 10 g of modified wrinkled graphene @Ti3C2-MXenes, 0.04 g of 2,2-dimethoxy-2-phenylacetophenone, and 5 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 50 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0062] S6. Preparation of fluorine-containing nano protective coating: 11 g of nano modifier, 95 g of polyurethane resin, 2.5 g of polyethylene glycol 400, 1.5 g of isooctyl alcohol and 150 g of cyclohexanone were stirred and mixed for 15 minutes, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0063] Example 4
[0064] Compared with Example 3, the difference is that the fluorine-containing siloxane is a single dodecafluoroheptylpropyltrimethoxysilane.
[0065] Example 5
[0066] Compared with Example 3, the difference is that the fluorine-containing siloxane is a single dodecafluoroheptylpropylmethyldimethoxysilane.
[0067] Comparative Example 1
[0068] Compared with Example 3, the difference is that step S1 is not performed.
[0069] The details are as follows:
[0070] S1. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 4 g Ti3C2-MXenes and 2.5 g graphene oxide were added to 100 mL water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0071] S2. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 4 g of fluorinated siloxane and 1.5 g of mercaptopropyl triethoxysilane were added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes were added. The mixture was heated to 50 ° C, stirred for 2 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes.
[0072] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 9:2.5;
[0073] S3. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes was reduced with hydrazine hydrate vapor for 8 h to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0074] S4. Click chemistry reaction: 10 g of modified wrinkled graphene @Ti3C2-MXenes, 0.04 g of 2,2-dimethoxy-2-phenylacetophenone, and 5 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 50 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0075] S5. Preparation of fluorine-containing nano protective coating: 11 g of nano modifier, 95 g of polyurethane resin, 2.5 g of polyethylene glycol 400, 1.5 g of isooctyl alcohol and 150 g of cyclohexanone were stirred and mixed for 15 min, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0076] Comparative Example 2
[0077] Compared with Example 3, the difference is that steps S2 and S4 are not performed.
[0078] The details are as follows:
[0079] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 4 g of tannic acid and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0080] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0081] S2. Preparation of fluorinated silane / mercaptosilane-modified Ti3C2-MXenes: 4 g of fluorinated siloxane and 1.5 g of mercaptopropyltriethoxysilane were added to 200 mL of ethanol, and 10 g of modified Ti3C2-MXenes were added. The mixture was heated to 50° C. and stirred for 2 h. The mixture was centrifuged, washed, and dried to obtain fluorinated silane / mercaptosilane-modified Ti3C2-MXenes.
[0082] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 9:2.5;
[0083] S3. Click chemistry reaction: 10 g of fluorinated silane / mercapto silane-modified Ti3C2-MXenes, 0.04 g of 2,2-dimethoxy-2-phenylacetophenone, and 5 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 50 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0084] S4. Preparation of fluorine-containing nano protective coating: 11 g of nano modifier, 95 g of polyurethane resin, 2.5 g of polyethylene glycol 400, 1.5 g of isooctyl alcohol and 150 g of cyclohexanone were stirred and mixed for 15 minutes, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0085] Comparative Example 3
[0086] Compared with Example 3, the difference is that no fluorine-containing silicone is added in step S3.
[0087] The details are as follows:
[0088] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 4 g of tannic acid and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0089] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0090] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 4 g of modified Ti3C2-MXenes and 2.5 g of graphene oxide were added to 100 mL of water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0091] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 5.5 g of mercaptopropyl triethoxysilane was added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes was added, heated to 50°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes;
[0092] S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes was reduced with hydrazine hydrate vapor for 8 h to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0093] S5. Click chemistry reaction: 10 g of modified wrinkled graphene @Ti3C2-MXenes, 0.04 g of 2,2-dimethoxy-2-phenylacetophenone, and 5 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 50 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0094] S6. Preparation of fluorine-containing nano protective coating: 11 g of nano modifier, 95 g of polyurethane resin, 2.5 g of polyethylene glycol 400, 1.5 g of isooctyl alcohol and 150 g of cyclohexanone were stirred and mixed for 15 minutes, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0095] Comparative Example 4
[0096] Compared with Example 3, the difference is that step S4 is not performed.
[0097] The details are as follows:
[0098] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 4 g of tannic acid and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0099] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0100] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 4 g of modified Ti3C2-MXenes and 2.5 g of graphene oxide were added to 100 mL of water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0101] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 4 g of fluorinated siloxane and 1.5 g of mercaptopropyl triethoxysilane were added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes was added, heated to 50°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes;
[0102] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 9:2.5;
[0103] S4. Click chemistry reaction: 10 g of modified oxidized wrinkled graphene @Ti3C2-MXenes, 0.04 g of 2,2-dimethoxy-2-phenylacetophenone, and 5 g of methyl acrylate were added to 200 mL of N,N-dimethylformamide, irradiated with ultraviolet light for 50 s, centrifuged, washed, and dried to obtain a nano-modifier;
[0104] S5. Preparation of fluorine-containing nano protective coating: 11 g of nano modifier, 95 g of polyurethane resin, 2.5 g of polyethylene glycol 400, 1.5 g of isooctyl alcohol and 150 g of cyclohexanone were stirred and mixed for 15 min, and evenly applied to the surface of the electronic motherboard. Ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0105] Comparative Example 5
[0106] Compared with Embodiment 3, the difference is that step S5 is not performed.
[0107] The details are as follows:
[0108] S1. Preparation of modified Ti3C2-MXenes: 10 g of Ti3C2-MXenes was added to 200 mL of water, 4 g of tannic acid and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified Ti3C2-MXenes;
[0109] The catalyst is a Tris-HCl solution with a pH of 8.5;
[0110] S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: 4 g of modified Ti3C2-MXenes and 2.5 g of graphene oxide were added to 100 mL of water, ultrasonically dispersed at 1500 W for 10 min, spray dried, and ball milled for 1 h to obtain wrinkled graphene oxide @Ti3C2-MXenes;
[0111] S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: 4 g of fluorinated siloxane and 1.5 g of mercaptopropyl triethoxysilane were added to 200 mL of ethanol, and 10 g of wrinkled graphene oxide @Ti3C2-MXenes was added, heated to 50°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide @Ti3C2-MXenes;
[0112] The fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane, with a mass ratio of 9:2.5;
[0113] S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes was reduced with hydrazine hydrate vapor for 8 h to obtain modified wrinkled graphene @Ti3C2-MXenes;
[0114] S5. Preparation of fluorine-containing nano protective coating: 11 g of modified wrinkled graphene @Ti3C2-MXenes, 95 g of polyurethane resin, 2.5 g of polyethylene glycol 400, 1.5 g of isooctyl alcohol and 150 g of cyclohexanone were stirred and mixed for 15 min, evenly applied to the surface of the electronic motherboard, and ventilated and cured for 7 days to obtain a fluorine-containing nano protective coating.
[0115] Test Example 1
[0116] The fluorine-containing nano protective coatings prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were tested for antifouling performance.
[0117] QUVB2000h is artificial radiation exposure UV aging for 2000 hours.
[0118] The results are shown in Table 1.
[0119] Table 1
[0120]
[0121]
[0122] It can be seen from the above table that the fluorine-containing nano protective coatings prepared in Examples 1-3 of the present invention have good anti-fouling properties.
[0123] Test Example 2
[0124] The fluorine-containing nano protective coatings prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were subjected to comprehensive performance tests.
[0125] Wear resistance test: The coating wear resistance test is carried out according to GB / T1768-2006.
[0126] Pencil hardness: According to the method of GB / T6739-2006, use pencils with gradually increasing hardness to draw across the coating surface at a 45° angle, and then observe the integrity of the coating surface until the coating surface is indented, scratched, or scratched. The hardness of the previous pencil is the hardness of the tested coating.
[0127] Adhesion test: According to the GB1720-2020 method, the coating integrity within the range of the circular roller line scratch is rated.
[0128] Contact angle test: The contact angle test was performed using an OCA40 contact angle meter from DataPhysics Instruments of Germany.
[0129] The results are shown in Table 2.
[0130] Table 2
[0131]
[0132]
[0133] It can be seen from the above table that the fluorine-containing nano protective coatings prepared in Examples 1-3 of the present invention have good comprehensive properties.
[0134] Test Example 3
[0135] The mechanical properties of the fluorine-containing nano protective coatings prepared in Examples 1-5 of the present invention and Comparative Examples 1-5 were tested.
[0136] According to GB / T 19250-2013 "Polyurethane Waterproof Coating" standard, the tensile speed is 500mm / min and the test temperature is 25℃.
[0137] The results are shown in Table 3.
[0138] Table 3
[0139] Group Tensile strength(MPa) Elongation at break (%) Example 1 8.15 652 Example 2 8.17 655 Example 3 8.22 658 Example 4 8.09 642 Example 5 8.04 645 Comparative Example 1 7.84 622 Comparative Example 2 7.78 605 Comparative Example 3 7.92 631 Comparative Example 4 7.82 620 Comparative Example 5 7.95 635
[0140] It can be seen from the above table that the fluorine-containing nano protective coatings prepared in Examples 1-3 of the present invention have good mechanical properties.
[0141] Test Example 4
[0142] The fluorine-containing nano protective coatings prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to the following performance tests.
[0143] The water resistance test refers to GB / T1733-1993 "Determination of water resistance of paint film", the test temperature is 40℃, and the test time is 24h.
[0144] The acid resistance is tested according to the immersion method specified in GB / T9274-1988 "Determination of resistance of paints and varnishes to liquid media", with a sulfuric acid mass fraction of 5%. Defects are observed after immersion for 24 hours.
[0145] The neutral salt spray resistance test is carried out in accordance with the provisions of GB / T1771-2007 "Determination of neutral salt spray resistance of paints and varnishes". The mass concentration of the sodium chloride solution is (50±5) g / L and the pH is 6.7±2.
[0146] The organic solvent resistance test is carried out according to the manual wiping method specified in GB / T23989-2009 "Determination of Solvent Resistance of Coatings by Wiping". Wipe back and forth 25 times with a finger wrapped in absorbent cotton to observe whether it is damaged and the base material is exposed.
[0147] The results are shown in Table 4.
[0148] Table 4
[0149]
[0150]
[0151] It can be seen from the above table that the fluorine-containing nano protective coatings prepared in Examples 1-3 of the present invention have good acid resistance, water resistance, salt spray resistance, and organic solvent resistance.
[0152] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a fluorine-containing nano protective coating, characterized in that: The surface of Ti3C2-MXenes is modified with tannic acid, coated with wrinkled graphene oxide, coupled with fluorine-containing siloxane and sulfur-containing silane coupling agents, and reduced to produce a surface click reaction to obtain a nano-modifier, which is then stirred and evenly mixed with polyurethane resin, dispersant, defoaming agent and solvent, and evenly applied to the surface of the electronic motherboard and maintained in a ventilated environment to obtain a fluorine-containing nano-protective coating.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: S1. Preparation of modified Ti3C2-MXenes: adding Ti3C2-MXenes to water, adding tannic acid and a catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain modified Ti3C2-MXenes; S2. Preparation of wrinkled graphene oxide @Ti3C2-MXenes: Add modified Ti3C2-MXenes and graphene oxide into water, disperse them uniformly by ultrasonication, spray dry them, and ball mill them to obtain wrinkled graphene oxide @Ti3C2-MXenes; S3. Preparation of modified wrinkled graphene oxide @Ti3C2-MXenes: adding fluorinated siloxane and sulfur-containing silane coupling agent into ethanol, adding wrinkled graphene oxide @Ti3C2-MXenes, heating and stirring to react, centrifuging, washing, and drying to obtain modified wrinkled graphene oxide @Ti3C2-MXenes; S4. Reduction: The modified wrinkled graphene oxide @Ti3C2-MXenes is reduced by hydrazine hydrate vapor to obtain modified wrinkled graphene @Ti3C2-MXenes; S5. Click chemistry reaction: adding modified wrinkled graphene @Ti3C2-MXenes, 2,2-dimethoxy-2-phenylacetophenone, and methyl acrylate into N,N-dimethylformamide, irradiating with ultraviolet light, centrifuging, washing, and drying to obtain a nano-modifier; S6. Preparation of fluorine-containing nano protective coating: stir and mix the nano modifier, polyurethane resin, dispersant, defoaming agent and solvent evenly, apply evenly to the surface of the electronic mainboard, and maintain under ventilation to obtain the fluorine-containing nano protective coating.
3. The preparation method according to claim 2, characterized in that: The mass ratio of Ti3C2-MXenes, tannic acid and catalyst in step S1 is 10:3-5:0.5-1, the temperature of the heating and stirring reaction is 40-50°C, the time is 2-4h, and the catalyst is a Tris-HCl solution with a pH of 8-9.
4. The preparation method according to claim 2, characterized in that: The mass ratio of the modified Ti3C2-MXenes and graphene oxide in step S2 is 3-5:2-3.
5. The preparation method according to claim 2, characterized in that: The mass ratio of the fluorinated siloxane, the sulfur-containing silane coupling agent, and the wrinkled graphene oxide @Ti3C2-MXenes in step S3 is 3-5:1-2:10, the temperature of the heated stirring reaction is 45-55°C, and the time is 1-3h. The fluorinated siloxane is selected from 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyl trimethoxysilane, dodecafluoroheptyl propyl trimethoxysilane, dodecafluoroheptyl propyl methyl dimethoxysilane, 3,3,3-trifluoropropyl methyl dimethoxysilane, 3,3,3-trifluoropropyl methyl dimethoxysilane, At least one of fluoropropyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane or 1H,1H,2H,2H-perfluorooctyltrimethoxysilane. Preferably, the fluorine-containing siloxane is a mixture of dodecafluoroheptylpropyltrimethoxysilane and dodecafluoroheptylpropylmethyldimethoxysilane in a mass ratio of 8-10:2-3. The sulfur-containing silane coupling agent is at least one of bis-(3-triethoxysilylpropyl)tetrasulfide, bis-(3-triethoxysilylpropyl)disulfide, mercaptopropyltriethoxysilane and γ-mercaptopropyltrimethoxysilane.
6. The preparation method according to claim 2, characterized in that: The time for the hydrazine hydrate steam reduction in step S4 is 7-10 hours.
7. The preparation method according to claim 2, characterized in that: In step S5, the mass ratio of the modified wrinkled graphene @Ti3C2-MXenes, 2,2-dimethoxy-2-phenylacetophenone, and methyl acrylate is 10: 0.03-0.05: 4-6, and the ultraviolet lamp irradiation time is 40-60s.
8. The preparation method according to claim 2, characterized in that: The mass ratio of the nano modifier, polyurethane resin, dispersant, defoamer and solvent in step S6 is 10-12:85-105:2-3:1-2:100-200, the solvent is selected from at least one of acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, dichloromethane, tetrahydrofuran, N,N-dimethylformamide and dioxane, the dispersant is selected from at least one of oleyl amino oleate, polyethylene glycol 600, polyethylene glycol 400 and sodium oleate, and the defoamer is selected from at least one of propylene glycol, isopropanol, n-butanol, isooctyl alcohol, naphtha and white mineral oil.
9. A fluorine-containing nano protective coating obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the fluorine-containing nano protective coating as claimed in claim 9 in the preparation of waterproof electronic products.
Citation Information
Patent Citations
Carbon fiber fabric composite material and preparation method thereof
CN111321587A
Preparation and application of MXenes biological coating with good biocompatibility
CN115177791A
Hybrid organic-inorganic two-dimensional metal carbide mxenes
WO2024044513A1
Cited By
Preparation method of high-weather-resistant wear-resistant rubber material for floating conveying pipe
CN120944339A